Methylcobalamin protects against liver failure via engaging gasdermin E - Wanfeng Xu; Yun Wang; Shuang Cui; Qiuling Zheng; Yanghao Lin; Qingqing Cui; Yuxin Xie; Yuming Zeng; Chuan Zhang; Yujie Li; Xin Jin; Minna Qin; et al. (Nature Communications)
Abstract Gasdermin E (GSDME) is a pyroptotic cell death effector and a promising target for pyroptotic tissue injury. Here we perform high-throughput screening and demonstrate that methylcobalamin (MeCbl), an endogenous coenzyme form of vitamin B12, is a specific GSDME inhibitor and highly effective against cholestatic liver failure. MeCbl specifically blocks GSDME cleavage by directly binding with GSDME. In cholestasis-, cisplatin- or concanavalin A (Con A)-induced male mouse models, MeCbl significantly suppresses liver transaminase activities and inflammation, alleviates hepatocyte death, and reduces mortality of mice by blocking GSDME cleavage. The conserved Cys180 residue in GSDME is essential for caspase-3/GzmB recognition. MeCbl in base-off conformation coordinates to Cys180 to prevent caspase-3/GzmB-GSDME interactions and thereby GSDME-mediated pyroptosis. In summary, our study discovers MeCbl as a specific GSDME inhibitor that is promisingly to be developed as an effective drug against cholestatic liver failure, and other GSDME triggered sterile inflammation and/or organ failure.